The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1063/1.858157
|View full text |Cite
|
Sign up to set email alerts
|

Long wave and lubrication theories for core-annular flow

Abstract: Different nonlinear amplitude equations for long waves in core-annular flow are compared. Each equation has its own limits of validity that can be critically assessed by comparing the linearization of approximate and exact theories. […printed abstract started this way.] We compare different nonlinear amplitude equations for long waves in core-annular flow. Each equation has its own limits of validity which can be critically assessed by comparing the linearization of approximate and exact theories. Long wave th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…We note that stabilization has also been observed in the infinite case where ''inertial'' pressures, arising from finite Reynolds number flows, have been identified as responsible. [13][14][15] To the extent that the symmetries of the infinite case are quite different, it may not surprise that the physics also differs.…”
Section: Discussionmentioning
confidence: 99%
“…We note that stabilization has also been observed in the infinite case where ''inertial'' pressures, arising from finite Reynolds number flows, have been identified as responsible. [13][14][15] To the extent that the symmetries of the infinite case are quite different, it may not surprise that the physics also differs.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the bifurcation theory are consistent with observations of flows that are close to perfect core-annular flows. We also present a review and critique of various weakly nonlinear long wave equations used to describe waves on the interface [Chen and Joseph 1991b]. Viscoelastic effects have been investigated by Chen [1991aChen [ , 1992.…”
Section: V4 Stability Studiesmentioning
confidence: 99%
“…Georgiou et al [18] and Kouris & Tsamopoulos [19,20] also found that when the core layer was more viscous than the annular layer, the shearing of basic flow acted to stabilize CAF at sufficiently high Reynolds numbers. Chen & Joseph [21] stated that the restraining effect of basic flow on capillary instability resulted from the fluid inertia.…”
mentioning
confidence: 99%